Mall (shopping centers) dynamics in bogotá (2005)
The current dynamics in the design, building and extension dynamics of Shoping Centers, that implies variations insize and area. This is a latinamerican phenomenon generate by the modernity project. This has to be re-thought from the different temporalities of society. This article is an approaching to this subject that examines main charactheristics of the Shoping Center dynamics and their social impact.